EFEKTIVITAS PELATIHAN PSIKOEDUKASI BERBASIS EXPERIENTIAL LEARNING DALAM MENINGKATKAN PEMAHAMAN MANAJEMEN KELAS GURU SD - Offie Dwi Natalia; Riana Sahrani; Heni Mularsih (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Tarumanagara, 2022)
Primary schools or Sekolah Dasar (SD) are the foundation of education in Indonesia. There, students are taught basic academic skills such as reading, writing, and counting; thus, professional and competent educators are in need. This research an act of intervention by increasing class management skills of the teachers in Public Elementary School X (Sekolah Dasar Negeri X), West Jakarta. In this research, class management is measured by observation, semi-structured interviews, and pretests. Participants of this research consists of 5 respondents, picked through a nonprobability sampling, with class management skills that are below average. The characteristics of the respondents are men and women aged between 22-43 with less than 10 years of teaching experience. This research utilizes the pretest-posttest experiment while providing psychoeducation based on experiential learning in order to increase the respondent’s class management skills. The data difference test from the pretest and posttest uses paired sample t-test, whereas t= -2.982 and p= 0.041 (0.05) which shows the respondent’s increased understanding of class management after being given 4.1% intervention. Through this research, it is concluded that psychoeducation based on experiential learning is effective in increasing SDN X educator’s class management skills.